Change in diversity and abundance of butterflies over five years of monitoring on the Zamorano Agroecological Farm - Bautista A., Stephany V. (Zamorano: Escuela Agrícola Panamericana, 2023)
Conventional agriculture has significant impacts on ecosystem health thus it is necessary to balance food production with preserving natural ecosystems. The present study analyzed the impact of agroecological practices on ecosystem health via long-term continuous monitoring of butterflies as bioindicators. Monitoring was done with replacement and mark recapture. A total of 2,843 individuals were captured and 90 species registered during 7 months from 2022 to 2023, yielding a 17% recapture rate. Even though only 13.95 ha of 40 ha are under land use change, there has been measurable impact on diversity, independent of seasonal patterns. Seasonality alters the abundance and diversity of butterflies due to food availability, habitat quality, and climate conditions. Time of the day (morning vs afternoon) did not influence capture frequencies. In addition, migratory species tend to alter population dynamics and increase apparent population size estimation during the early dry season.